2018
DOI: 10.1007/s00359-018-1289-6
|View full text |Cite
|
Sign up to set email alerts
|

Independent processing of increments and decrements in odorant concentration by ON and OFF olfactory receptor neurons

Abstract: A salient feature of the insect olfactory system is its ability to detect and interpret simultaneously the identity and concentration of an odorant signal along with the temporal stimulus cues that are essential for accurate odorant tracking. The olfactory system of the cockroach utilizes two parallel pathways for encoding of odorant identity and the moment-to-moment succession of odorant concentrations as well as the rate at which concentration changes. This separation originates at the peripheral level of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 88 publications
(117 reference statements)
0
19
0
1
Order By: Relevance
“…One prominent example is the split into ON and OFF pathways, where individual neurons become selective to either increases (ON) or decreases (OFF) in a signal. Such an ON/OFF dichotomy enables more efficient coding of stimuli in the visual system (Gjorgjieva et al, 2014) and occurs across many different species and sensory modalities, such as vision, olfaction, audition, thermosensation, and electrolocation (Bennett, 1971; Gallio et al, 2011; Scholl et al, 2010; Tichy and Hellwig, 2018; Werblin and Dowling, 1969). Examples of how the split into ON and OFF pathways is implemented in sensory information processing have already been described.…”
Section: Introductionmentioning
confidence: 99%
“…One prominent example is the split into ON and OFF pathways, where individual neurons become selective to either increases (ON) or decreases (OFF) in a signal. Such an ON/OFF dichotomy enables more efficient coding of stimuli in the visual system (Gjorgjieva et al, 2014) and occurs across many different species and sensory modalities, such as vision, olfaction, audition, thermosensation, and electrolocation (Bennett, 1971; Gallio et al, 2011; Scholl et al, 2010; Tichy and Hellwig, 2018; Werblin and Dowling, 1969). Examples of how the split into ON and OFF pathways is implemented in sensory information processing have already been described.…”
Section: Introductionmentioning
confidence: 99%
“…Neuroanatomical and electrophysiological studies show that these sensilla are located on the distal and proximal margins of each of the 120–180 antennal segments. They make up about 6% of the olfactory sensilla in the male cockroach (Schaller, 1978; Burgstaller and Tichy, 2012; Tichy and Hellwig, 2018). Inserting the tip of a needle electrode into the sensillum base enables recording the action potentials of both ORN types at the same time.…”
Section: Resultsmentioning
confidence: 99%
“…In this way, concentration increments and decrements are encoded by excitatory signals. During slow and continuous concentration changes, both types of ORNs not only signal the moment-to-moment succession of odorant concentrations but also the rate at which concentration changes (Burgstaller and Tichy, 2011, 2012; Tichy and Hellwig, 2018). Furthermore, the rate of concentration change modulates the gain of responses for fluctuations in the odorant concentration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Does an increase in the rate of concentration increase determine the ORNs performance in detecting concentration differences along a gradient? There is no definite answer, but electrophysiological experiments with a specific type of ON and OFF ORNs located in morphologically identifiable single-walled trichoid (swC) sensilla on the cockroach's antenna revealed that the differential sensitivity or the gain of responses for the rate of concentration change decreases rather than increases with rising rate of change (Burgstaller and Tichy, 2012;Tichy et al, 2016;Tichy and Hellwig, 2018). The high gain for slow rates of change improves the cockroach's ability to detect slowly fluctuating or creeping concentration changes which persist in one direction.…”
Section: Introductionmentioning
confidence: 99%